LIMNOLOGICAL CONDITION AND ESTIMATION OF POTENTIAL FISH PRODUCTION OF KERINCI LAKE JAMBI, SUMATRA - Samuel Samuel; Ni Komang Suryati; Vipen Adiansyah (Indonesian Fisheries Research Journal, 2015)
Kerinci Lake is a type of tectonic lakes located in a protected forest area of National Park of Kerinci Sebelat and a source of various fish species important for local people for their dayly food comsumption and income. However, few information is available on limnological condition and fish resources. Field research observing the limnological condition and estimating the potential fish production was conducted four times in April, June, August and October 2013. The research is aimed to describe the condition of limnology and estimate the potential fish production of the lake. Limnological aspect included the physico-chemical and biological parameters, namely: temperature, water transparency, depth, substrate, conductivity, pH, dissolved oxygen, alkalinity, ammonia, nitrate, phosphate, total phosphorus, chlorophyll-a and trophic state. Potential fish production was calculated by using the biological parameter levels of chlorophyll-a. The results show that the euphotic layer of the lake waters was still feasible for fish life. Water condition of the bottom layer was less supportable for fish life due to low dissolved oxygen content. Trophic state index (TSI) values, either measured by temporal and spatial ways, had TSI with an average of 61.75. From these index, the lake is classified as a lake at the high productivity level (eutrophic). Annual fish production was an average of 307 kg/ha/year. By taking account the average of fish production and the total area of lake of around 4,200 ha, the potential fish production of Kerinci Lake is estimated about ± 1,287 tons/year.